2019
DOI: 10.1186/s43055-019-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

‘Triple-rule-out’ CT angiography for clinical decision making and early triage of acute chest pain patients: use of 320-multislice CT angiography

Abstract: Background: In our study, we aimed to estimate utility of TRO CTA to guide clinical decision in acute chest pain patients with intermediate risk to acute coronary syndrome (ACS) in the emergency department.Methods and material: Our study population included 45 acute chest pain patients with intermediate-risk ACS. All these patients had done TRO CTA to access any pathological conditions in the coronary artery, pulmonary artery, aorta and thoracic diseases that may be the cause of their complaint. Follow-up was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Our study revealed that TRO CTA is an effective and non-invasive diagnostic method in COVID-19 patients who were admitted to the ED with acute chest pain. Acute chest pain might be due to pneumonia itself or accompanying vascular events which are related to an increased risk of thrombosis, endothelial dysfunction, and myocardial injury in COVID-19 cases[ 5 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study revealed that TRO CTA is an effective and non-invasive diagnostic method in COVID-19 patients who were admitted to the ED with acute chest pain. Acute chest pain might be due to pneumonia itself or accompanying vascular events which are related to an increased risk of thrombosis, endothelial dysfunction, and myocardial injury in COVID-19 cases[ 5 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our center, TRO CTA examination is performed according to the eligibility criteria in the article of Eltabbakh AR et al [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is a useful method for the exclusion and the diagnosis of CAD, PTE, and AAS with high specificity; hence, it can play an important role in decision-making in the ED. TRO-CT can define CAD and PTE with a satisfying sensitivity and specificity in comparison with dedicated protocols [19,20]. We have used basically a similar protocol with TRO-CT, with the addition of DECT, to assess myocardial perfusion deficits.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Triple rule-out CT has been a helpful and effective tool in the arsenal of emergency physicians in diagnosing cases of concern and determining the patient population which can be sent home without further cardiac testing. 9 13 The present study aims to quantify the diagnostic yield of TRO-CT in evaluating acute chest pain in patients presenting to the emergency department of a tertiary care hospital and revive and impart the knowledge on TRO-CT to our fellow emergency physicians and residents in India.…”
Section: Introductionmentioning
confidence: 99%